Maternal Knowledge and Family Support in Measles Immunization: Pengetahuan Ibu dan Dukungan Keluarga dalam Imunisasi Campak - Tri Anisa Istiqomah; Kartika Ishartadiati; Akhmad Sudibja; Jesyca Isabel Anggraini; Puput Ayu Novitasari (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Measles remains a significant public health problem despite the availability of safe and effective vaccination programs, particularly among children under five years of age. Specific Background: The success of measles immunization at community-based health services such as Posyandu is associated with maternal knowledge and family support as key determinants of child health decisions. Knowledge Gap: However, empirical evidence at the rural primary healthcare level, especially in Gayam Village Posyandu, remains limited regarding how these factors relate to measles immunization provision. Aims: This study aimed to analyze the relationship between maternal knowledge and family support with measles immunization among children aged 9–18 months in Gayam Village Posyandu. Results: Using a quantitative cross-sectional design with 33 randomly selected mothers, data were collected through structured questionnaires and analyzed using the Chi-square test. Most respondents demonstrated high maternal knowledge (97%), whereas 69.7% reported poor family support. Statistical analysis showed no significant association between maternal knowledge and measles immunization (p = 0.179) nor between family support and measles immunization (p = 0.364). Novelty: This study provides localized empirical evidence from a rural Posyandu setting, highlighting the contextual dynamics of maternal and family-related factors in measles vaccination decisions. Implications: These findings indicate that high knowledge levels alone are insufficient to ensure immunization uptake and underscore the need for family-centered and community-based strategies to strengthen measles immunization coverage at the primary healthcare level. Highlights: The majority of respondents demonstrated high cognitive understanding of measles vaccination. Most participants reported inadequate household encouragement in child health decisions. Statistical testing identified no significant relationship between the examined variables and vaccine administration. Keywords: Maternal Knowledge, Family Support, Measles Immunization, Toddler, Posyandu.